Assessment of voice, speech and communication changes associated with cervical spinal cord injury. Issue 4 (24th February 2018) - Johansson, Kerstin; Seiger, Åke; Forsén, Malin; Holmgren Nilsson, Jeanette; Hartelius, Lena; Schalling, Ellika
Abstract: Background: Respiratory muscle impairment following cervical spinal cord injury (CSCI) may lead to reduced voice function, although the individual variation is large. Voice problems in this population may not always receive attention since individuals with CSCI face other, more acute and life‐threatening issues that need/receive attention. Currently there is no consensus on the tasks suitable to identify the specific voice impairments and functional voice changes experienced by individuals with CSCI. Aims: To examine which voice/speech tasks identify the specific voice and communication changes associated with CSCI, habitual and maximum speech performance of a group with CSCI was compared with that of a healthy control group (CG), and the findings were related to respiratory function and to self‐reported voice problems. Methods & Procedures: Respiratory, aerodynamic, acoustic and self‐reported voice data from 19 individuals (nine women and 10 men, aged 23–59 years, heights = 153–192 cm) with CSCI (levels C3–C7) were compared with data from a CG consisting of 19 carefully matched non‐injured people (nine women and 10 men, aged 19–59 years, heights = 152–187 cm). Outcomes & Results: Despite considerable variability of performance, highly significant differences between the group with CSCI and the CG were found in maximum phonation time, maximum duration of breath phrases, maximum sound pressure level and maximum voice area in voice‐range profiles (all p = .000). Subglottal pressure was lower and phonatory stability was reduced in some of the individuals with CSCI, but differences between the groups were not statistically significant. Six of 19 had voice handicap index (VHI) scores above 20 (the cut‐off for voice disorder). Individuals with a vital capacity below 50% of the expected for an equivalent reference individual performed significantly worse than participants with more normal vital capacity. Completeness and level of injury seemed to impact vocal function in some individuals. Conclusions & Implications: A combination of maximum performance speech tasks, respiratory tasks and self‐reported information on voice problems help to identify individuals with reduced voice function following CSCI. Early identification of individuals with voice changes post‐CSCI, and introducing appropriate rehabilitation strategies, may help to minimize development of maladaptive voice behaviours such as vocal strain, which can lead to further impairments and limitations to communication participation.